Haemoglobin as a biomarker for clinical outcomes in chronic obstructive pulmonary disease. Issue 3 (26th July 2021) - Balasubramanian, Aparna; Henderson, Robert J.; Putcha, Nirupama; Fawzy, Ashraf; Raju, Sarath; Hansel, Nadia N.; MacIntyre, Neil R.; Jensen, Robert L.; Kinney, Gregory L.; Stringer, William W.; Hersh, Craig P.; Bowler, Russell P.; et al.
In COPD, anaemia is associated with increased morbidity, but the relationship between haemoglobin over its entire observed range and morbidity is poorly understood. Such an understanding could guide future therapeutic targeting of haemoglobin in COPD management. Leveraging the COPDGene study, we conducted a cross-sectional analysis of haemoglobin from COPD participants, examining symptoms, quality of life, functional performance, and acute exacerbations of COPD (AECOPD). Haemoglobin was analysed both as a continuous variable and categorised into anaemia, normal haemoglobin, and polycythaemia groups. Fractional polynomial modelling was used for continuous analyses; categorical models were multivariable linear or negative binomial regressions. Covariates included demographics, comorbidities, emphysema, diffusing capacity, and airflow obstruction. From 2539 participants, 366 (14%) were identified as anaemic and 125 (5%) as polycythaemic. Compared with normal haemoglobin, anaemia was significantly associated with increased symptoms (COPD Assessment Test score: p=0.006, modified Medical Research Council (mMRC) Dyspnoea Score: p=0.001); worse quality of life (St. George's Respiratory Questionnaire (SGRQ) score: p<0.001; Medical Outcomes Study Short Form 36-item Questionnaire (SF-36) General Health: p=0.002; SF-36 Physical Health: p<0.001), decreased functional performance (6-min walk distance (6MWD): p<0.001), and severe AECOPD (p=0.01), while polycythaemia was not. Continuous models, however, demonstrated increased morbidity at both ends of the haemoglobin distribution (p<0.01 for mMRC, SGRQ, SF-36 Physical Health, 6MWD, and severe AECOPD). Evaluating interactions, both diffusing capacity and haemoglobin were independently associated with morbidity. We present novel findings that haemoglobin derangements towards either extreme of the observed range are associated with increased morbidity in COPD. Further investigation is necessary to determine whether haemoglobin derangement drives morbidity or merely reflects systemic inflammation, and whether correcting haemoglobin towards the normal range improves morbidity. Haemoglobin is nonlinearly associated with clinical outcomes in COPD, with increased morbidity at either extreme of the observed range, suggesting that therapeutic correction of anaemia might be most beneficial if targeting normal haemoglobin values https://bit.ly/3ovl7Lt